REVITALISASI PASAR IKAN TRADISIONAL KAMPUNG NELAYAN TANJUNG UMAH KEPULAUAN RIAU - Stivani Ayuning Suwarlan; Yustisio Mahendra; Jennie Jennie; Irene Irene; Jacky Jacky; Lovianna Lovianna; Feby Trisna; Justyanita Justyanita; Darryl Darryl; Kelty Joria; Muhammad Syachrani Hafidz (National Conference for Community Service Project (NaCosPro), 2020)
Tanjung Umah's traditional fish market in the Riau Islands is no longer attractive to the public because the fish are not neatly arranged and the market conditions look less clean. The lack of interest in traditional fish markets has led to a decline in local community income in the Tanjung Umah village. Therefore, this social community empowerment activity program aims to revive (revitalize) the traditional fish market so that it is again in demand by the community and change the negative perceptions of the traditional fish market through the design of an apron that gives identity to the traditional fish market of the Tanjung Umah fishing village in Riau Islands while maintaining the sellers to avoid fish waste so that it looks clean and hygienic. Through the use of this apron, the traditional fish market of Tanjung Umah fishing village can look tidier, in uniform, and attractive so that it can return to life and be of interest to the community.